The effect of electric field on the formation of hydroxyapatite coatings - Peaker, A; Czernuszka, J (1996)
A method using the action of an electric field on a continuously precipitating solution of calcium phosphate has been used to obtain reproducible hydroxyapatite coatings (1-2 μm) on a stainless steel substrate. The effect of changing various parameters on the nature of the coating was ascertained including constant current and constant voltage conditions, temperature, supersaturation and electrode spacing. The resultant coatings were characterised using electron microscopical and X-ray diffraction techniques. The mechanical properties were tested using a microhardness indentation technique, the results from which were used to give some indication of the strength and adhesion of the coatings. A model has been proposed to explain the observed phenomena in the precipitation and deposition processes. Amorphous calcium phosphate forms initially in the form of spheres. These spheres coalesce to form gel-like sheets in which hydroxyapatite nucleates. The gel sheets are attracted electrophoretically to the cathode where they are deposited as cells. Each cell wall comprises a number of 100 nm sized crystals oriented with their c-axis perpendicular to the substrate surface.